PENDIDIKAN ISLAM WASATHIYAH: HUMANIORA SEBAGAI JEMBATAN MODERASI BERAGAMA - Fachrizal Fachrizal (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
Wasathiyah (moderate) Islamic education faces significant challenges amid increasing polarization in religious thought and the growing complexity of cultural globalization. This article explores the strategic role of the humanities including literature, philosophy, art, and history in reinforcing religious moderation within Islamic Religious Education (PAI). Using a qualitative approach based on library research and limited case studies in several Islamic educational institutions in Indonesia, the study identifies three major contributions of humanities integration. First, the humanities facilitate students' critical thinking in interpreting religious texts and contexts more reflectively. Second, the humanities nurture empathy and appreciation for diversity through inclusive narratives and artistic expressions. Third, the humanities-based approach proves effective in mitigating tendencies toward radicalism through multidisciplinary discussions that challenge binary religious understandings. The findings offer a fresh conceptual framework for Islamic education policymakers to respond more effectively to contemporary needs by promoting a more dialogical, contextual, and humanistic PAI curriculum. Thus, religious education can evolve from being solely normative-doctrinal to becoming a platform for cultivating moderate and transformative social consciousness.